Aspects and possibilities about the use of digital technologies in Statistical Education: discussions based on Nepso's methodology - Felipe Júnio de Souza Oliveira (Universidade Federal do Oeste da Bahia, 2020)
Digital technologies have intensified the production and access to information available worldwide. The intense and growing traffic of digital content carries with it a significant amount of statistical concepts propagated by means of communication and interaction. Interested in this theme, we selected part of a research to highlight and discuss the use of technologies in Statistical Education. For that, some aspects and possibilities are analyzed with a view to statistical literacy. From the perspective of the methodology of the "our school survey your opinion" program (Nepso), some results of the use of WhatsApp, Facebook and Excel in opinion educative survey, carried out by elementary school students, are explored with a view to reflecting on the contributions and limitations of technologies in statistical learning. Thus, it is concluded, among other things, that Nepso, combined with the use of these technologies, is an important didactic investment for Statistical Education.